Biathlon Injury and Illness Surveillance project (BIIS): development of biathlon-specific surveillance forms in English, Russian, French and German. Issue 1 (14th November 2019) - Van Dyk, Carlee; Panagodage Perera, Nirmala; Carrabre, James E; Manfredini, Fabio; Fitzpatrick, Jane
Abstract : Objective: The aim of this project was to adapt the English, French, German and Russian versions of the International Olympic Committee ( IOC ) injury and illness surveillance form to be sport-specific for use in biathlon. Methods: 23 medical representatives from 16 of the 55 biathlon federations participated in this project to adapt the form and create disease coding relevant to biathlon. The English version of the IOC injury and illness surveillance form was used as the primary template. Four review rounds were used to develop electronic fillable PDF forms. The changes were then forward translated onto the Russian, French and German forms. Results: Changes were made to event type to biathlon-specific events. A weekly reporting format was adopted in line with the race week format of World Cup events. Wherever possible, coding replaced free-text format to avoid translation issues. New codes were created to describe the time of injury/illness. A new symptom code was added to reflect the prevalence of respiratory infection: sore throat/cold symptoms. As the number of athletes in a team differs between weeks in the season, an additional question was added to ask for the 'number of athletes in the team for the week' and for the season. Conclusion: This project provides a biathlon-specific injury and illness surveillance form in English, French, German and Russian. This forms the basis for surveillance that will contribute to a greater understanding of the illness and injury rate in elite biathletes and ultimately to enhanced athlete well-being and success in biathlon, and winter sports more generally.